A Reflection on Practical Innovation Beyond COVID - Bettine Ortmann (Journal of Innovation in Polytechnic Education)
In January 2020, I kicked off the research for an innovation project at the Copenhagen School of Design and Technology (KEA). I went to NRF in New York together with 40.000 other curious practitioners and academics wanting to explore the latest trends within retail. Commerce was going online – the landscape of physical retail was changing dramatically from places of transactions to spaces for experiences. Physical experiences that called for a totally new approach to retail. The scope of my innovation project was to get insights into this trend and best practices and to develop an intuitive and easy guide on how to use the physical space as a brand channel. I was highly motivated to embark on the research project – my biggest challenge was to find time for doing all the research. My spring was jam-packed with physical lecturing and other stuff going on. Then COVID hit the world.